Studying the effect of adding a mixture of metal oxides to paraffin wax and using it as solar energy cells and corrosion inhibitors. - hasan, Tabarak saad; Al-Abdaly, Basim Ibrahim (Iraqi Journal of Science, 2025)
In this study, nanoparticles of metal oxides (CoO, NiO, and TiO2) were synthesized using the hydrothermal method. These nanoparticles were then incorporated into paraffin wax, serving as a matrix, to create nanocomposites. The resulting materials, [TiO2; CoO/paraffin] and [TiO2; NiO/paraffin], were prepared using ultrasonic techniques. The morphology, size, and structures of the synthesized nanocomposites were examined and characterized using atomic force microscopy (AFM), field emission scanning electron microscopy with energy dispersive spectroscopy (FESEM-EDS), energy dispersive X-ray (EDX), X-ray diffraction (XRD), Fourier transformer infrared (FT-IR), and ultraviolet-visible (UV-Vis) spectroscopy to confirm the design of nanocomposites based nanostructures and reveal their distinctive features from there distribution on paraffin wax. The results of AFM for the two synthesized nanostructures [TiO2; CoO/paraffin], [TiO2; NiO/paraffin], showed that nanoparticles were in the nanoscale (87.54 nm, and 56.74 nm) respectively. The three-dimensional images depict heterogeneous grooves in all nanostructures of the synthesized composites. This is primarily attributed to the agglomeration of metal oxide nanoparticles, which results in some of the paraffin surface being covered. The activities of nanocomposites synthesized were studied from the industrial side, including solar cell energy and the use of these nanocomposites as inhibitors for corrosion. The findings for all of these nanocomposites revealed they have the properties of solar cells and a significant inhibitory effect.